(untitled) (Studia austriaca, 2013)
This article addresses the relation of Zerreißprobe (1970), the last performance work of the Viennese Actionist Günter Brus, to the tradition of Christian self-sacrifice. Three aspects of this relation are given particular attention: the aestheticization of suffering, the representative function of sacrifice and the distinction between the dependent body and the postulate of free will.